2021
DOI: 10.1002/ecy.3495
|View full text |Cite
|
Sign up to set email alerts
|

Shared friends counterbalance shared enemies in old forests

Abstract: Mycorrhizal mutualisms are nearly ubiquitous across plant communities. Yet, it is still unknown whether facilitation among plants arises primarily from these mycorrhizal networks or from physical and ecological attributes of plants themselves. Here, we tested the relative contributions of mycorrhizae and plants to both positive and negative biotic interactions to determine whether plant-soil feedbacks with mycorrhizae neutralize competition and enemies within multitrophic forest community networks. We used Bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 111 publications
(289 reference statements)
0
9
0
Order By: Relevance
“…The effects of drought (reduced plant‐available water) are filtered through fine‐grained ecological attributes including microtopography, soil water‐holding capacity, and forest density (affecting water demand), and these fine‐grained conditions can potentially mediate the realized microenvironment that trees experience. Tree neighborhoods capture this net drought effect along with resource competition and spatially nonrandom mortality processes, all factors that are all closely linked to tree‐to‐tree variance in mortality risk (Furniss, Larson, et al, 2020; Germain & Lutz, 2021; van Mantgem et al, 2018). Other studies have similarly shown the importance of both climate and forest structure to mortality risk (Restaino et al, 2019; Ruiz‐Benito et al, 2013; van Mantgem et al, 2018; Young et al, 2017), but few directly compare the relative magnitude of their effects.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of drought (reduced plant‐available water) are filtered through fine‐grained ecological attributes including microtopography, soil water‐holding capacity, and forest density (affecting water demand), and these fine‐grained conditions can potentially mediate the realized microenvironment that trees experience. Tree neighborhoods capture this net drought effect along with resource competition and spatially nonrandom mortality processes, all factors that are all closely linked to tree‐to‐tree variance in mortality risk (Furniss, Larson, et al, 2020; Germain & Lutz, 2021; van Mantgem et al, 2018). Other studies have similarly shown the importance of both climate and forest structure to mortality risk (Restaino et al, 2019; Ruiz‐Benito et al, 2013; van Mantgem et al, 2018; Young et al, 2017), but few directly compare the relative magnitude of their effects.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal communities can influence the productivity, composition and health of forests through cycling nutrients, providing resources and pathogen introduction or, in the case of mycorrhizal fungi, protection from pathogens (Tedersoo et al, 2020). Thus, shifts in fungal communities could impact forests by altering interactions between trees and their environments (Germain & Lutz, 2021). Identifying the types of assembly and the variation in assembly processes can provide insight within the studied system and help generalize the drivers of deterministic and neutral processes across systems.…”
Section: Introductionmentioning
confidence: 99%
“…We found net negative heterospecific effects with climate warming, suggesting that any underlying positive interactions (e.g., shared mycorrhizal networks; Bennett et al, 2017) were unable to completely offset increasingly negative interactions among the tree species. Silvicultural interventions that cultivate enhanced facilitation among heterospecifics (Germain & Lutz, 2021; Jactel & Brockerhoff, 2007) may be able to counteract negative interactions and conserve forest community stability.…”
Section: Discussionmentioning
confidence: 99%